(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
Vowels are an essential component of speech sounds, forming the core of every syllable in a word. They are produced with an open vocal tract, allowing air to flow freely without any significant obstruction. However, vowels are not static; they can be modified in various ways to create different sounds and convey different meanings. In this article, we will explore the modifications that vowels undergo and their significance in language.